The relationship among tourism, poverty, and economic development in developing countries: A panel data regression analysis. (December 2016) - Kim, Namhyun; Song, HakJun; Pyun, Ju Hyun
This study investigates the relationship among tourism, poverty, and economic development in developing countries. The empirical model is set up using unbalanced panel observations for 69 developing countries for the period 1995–2012. The findings show that tourism has heterogeneous effects on the poverty ratio in terms of a country's income per capita: the positive effect of tourism on poverty alleviation switches to being negative after a certain threshold of a country's income level. The results of this study indicate that only the least developed countries (those with an income per capita below international dollar 3400) have benefited from the tourism industry in terms of reducing their poverty ratios.